A Disposable Tear Glucose Biosensor—Part 5: Improvements in Reagents and Tear Sampling Component. (July 2018) - Lin, Chi En; Ito, Yuka; Deng, Anna; Johns, Jared; Matloff, Daniel; Cook, Curtiss B.; Sode, Koji; La Belle, Jeffrey T.
A tear glucose (TG) sensor with an integrated tear sampler can provide a noninvasive method for calibrating the continuous TG contact lens and monitoring glucose. Expanding from previous work, an improved TG sensor that implements dried reagents, genetically modified glucose dehydrogenase (GDH), and a tear sampler was developed and compared against the TG sensor prepared with commercial GDH. It was found that neither sensor was affected by the tear interferents: ascorbic acid, acetaminophen, and uric acid. The sensor prepared with commercial GDH generated higher current. This suggests that using enzymes with lower Km may be advantageous when operating in low glucose environments like tears. The improved TG sensor also demonstrated the potential of integrating Schirmer's test strip as a tear sampler for self-monitoring of TG.